Measurements of the z > 5 Lyman-α forest flux autocorrelation functions from the extended XQR-30 data set - Wolfson, Molly; Hennawi, Joseph F.; Bosman, Sarah; Davies, Frederick B.; Lukić, Zarija; Becker, George D.; Chen, Huanqing; Cupani, Guido; D’Odorico, Valentina; Eilers, Anna-Christina; Haehnelt, Martin G.; Keating, Laura C.; et al. (Monthly notices of the Royal Astronomical Society, 2024)
We present the first observational measurements of the Lyman-α (Ly α) forest flux autocorrelation functions in ten redshift bins from 5.1 ≤ z ≤ 6.0. We use a sample of 35 quasar sightlines at z > 5.7 from the extended XQR-30 data set; these data have signal-to-noise ratios of >20 per spectral pixel. We carefully account for systematic errors in continuum reconstruction, instrumentation, and contamination by damped Ly α systems. With these measurements, we introduce software tools to generate autocorrelation function measurements from any simulation. Our measurements of the smallest bin of the autocorrelation function increase with redshift when normalizing by the mean flux, 〈F〉. This increase may come from decreasing 〈F〉 or increasing mean free path of hydrogen-ionizing photons, λmfp. Recent work has shown that the autocorrelation function from simulations at z > 5 is sensitive to λmfp, a quantity that contains vital information on the ending of reionization. For an initial comparison, we show our autocorrelation measurements with simulation models for recently measured λmfp values and find good agreements. Further work in modelling and understanding the covariance matrices of the data is necessary to get robust measurements of λmfp from this data.
Gesehen am 15.08.2025